Determinants of the intention to vaccinate with MMR among pregnant women from the City of Rome. (13th November 2019) - Rosso, A; Massimi, A; Baccolini, V; Pitini, E; Marzuillo, C; Vito, C De; Villari, P
Abstract: Background: Further to the increase in measles cases reported in Italy since 2016, MMR vaccination became mandatory in 2017, leading to an increase in vaccination coverage in the Country. To guarantee sustained coverage, factors influencing the intention to vaccinate in the population should be better understood. Methods: We conducted a cross-sectional survey to assess knowledge and attitudes on pediatric vaccinations and intention to vaccinate among pregnant women attending Antenatal Classes in Rome, through distribution of a self-administered questionnaire, which included a specific section on MMR vaccination. Multiple logistic regression analysis was performed to analyze the determinants of the intention to vaccinate with MMR. Results: A total of 458 pregnant women attending CANs in 36 family health centers and two hospitals answered the survey. Intention to vaccinate with MMR was associated with having received information from a healthcare professional (OR 1.92, 95%CI 1.01-3.63), the perceived importance of vaccines to protect against measles (OR 4.68, 95%CI 2.48- 9.54) and rubella (OR 5.97, 95%CI 2.98-11.95), not believing in news about the risks of MMR vaccine (OR 2.75, 95%CI 1.38-5.50), and the sense of guilt in case the child should contract the disease (OR 2.56, 95%CI 1.16-5.62). Factors negatively associated with the intention to vaccinate were the use of alternative medicine (OR 0.34, 95%CI 0.16- 0.76), believing that MMR vaccine can have serious side effects (OR 0.37, 95%CI 0.00-0.29) and guilt in case of serious side effects (OR 0.40, 95%CI 0.21-0.76). Conclusions: Fear of MMR side effects is a relevant driver of the intention to vaccinate, coupled with the perceived importance to vaccinate to protect against measles and rubella. Also the source of information plays an important role in shaping ideas on vaccines. Information and communication strategies should be promoted to increase trust in vaccines, with a direct involvement of healthcare workers. Key messages: Fear of MMR side effects and perceived benefits of the vaccine influence the intention to vaccinate. Information and communication strategies to increase vaccination appectance involving healthcare workers are needed.